Adolescent with Human Immunodeficiency Virus - understanding family beliefs and values - Patrícia Neyva da Costa Pinheiro; Clarice Mendes de Freitas; Ligia Fernandes Scopacasa; Kelanne Lima da Silva; Fabiane do Amaral Gubert; Izaildo Tavares Luna (Rev Rene)
Objective: to understand how the beliefs and values of the families of HIV-positive adolescents for Human Immunodeficiency Virus influence family dynamics. Methods: this is a qualitative research with seven family members of adolescents with Human Immunodeficiency Virus, developed in a hospital of reference in infectious diseases. A semi-structured interview was used to collect information. Qualitative research assumptions were applied and the Consolidated Criteria for Reporting Qualitative Research protocol was used for organization and analysis. Results: the family members reported that the adolescents are not perceived as susceptible to infection by the Human Immunodeficiency Virus; they considered AIDS to be a serious disease surrounded by discrimination and prejudice; they identify benefits as guidelines for health and family support. The barriers were difficulty adhering to treatment, teenage pregnancy, “disobedience” and family disharmony. Conclusion: beliefs and values interfere in the way of thinking, acting and caring for the HIV positive adolescent to the Human Immunodeficiency Virus.